Use your power for good: plural valuation of nature – the Oaxaca statement - Jacobs, S.; Zafra-Calvo, Noelia; González Jimenez, D.; Guibrunet, L.; Benessaiah, K.; Berghöfer, A.; Chaves-Chaparro, J.; Díaz, S.; Gómez Baggethun, E.; Lele, S.; Martín López, B.; Masterson, V.A.; et al. (Cambridge University Press, 2020)
Decisions on the use of nature reflect the values and rights of individuals, communities and society at large. The values of nature are expressed through cultural norms, rules and legislation, and they can be elicited using a wide range of tools, including those of economics. None of the approaches to elicit peoples’ values are neutral. Unequal power relations influence valuation and decision-making and are at the core of most environmental conflicts. As actors in sustainability thinking, environmental scientists and practitioners are becoming more aware of their own posture, normative stance, responsibility and relative power in society. Based on a transdisciplinary workshop, our perspective paper provides a normative basis for this new community of scientists and practitioners engaged in the plural valuation of nature.